Coordination of autonomic and endocrine stress responses to the Trier Social Stress Test in adolescence. (30th March 2022) - Glier, Sarah; Campbell, Alana; Corr, Rachel; Pelletier‐Baldelli, Andrea; Yefimov, Mae; Guerra, Carina; Scott, Kathryn; Murphy, Louis; Bizzell, Joshua; Belger, Aysenil
Abstract: Dysregulations in autonomic and endocrine stress responses are linked to the emergence of psychopathology in adolescence. However, most studies fail to consider the interplay between these systems giving rise to conflicting findings and a gap in understanding adolescent stress response regulation. A multisystem framework—investigation of parasympathetic (PNS), sympathetic (SNS), and hypothalamic pituitary adrenal (HPA) axis components and their coordination—is necessary to understand individual differences in stress response coordination which contribute to stress vulnerabilities. As the first investigation to comprehensively evaluate these three systems in adolescence, the current study employed the Trier Social Stress Test in 72 typically developing adolescents (mean age = 13) to address how PNS, SNS, and HPA stress responses are coordinated in adolescence. Hypotheses tested key predictions of the Adaptive Calibration Model (ACM) of stress response coordination. PNS and SNS responses were assessed via heart rate variability (HRV) and salivary alpha amylase (sAA) respectively. HPA responses were indexed by salivary cortisol. Analyses utilized piecewise growth curve modeling to investigate these aims. Supporting the ACM theory, there was significant hierarchical coordination between the systems such that those with low HRV had higher sAA and cortisol reactivity and those with high HRV had low‐to‐moderate sAA and cortisol responsivity. Our novel results reveal the necessity of studying multisystem dynamics in an integrative fashion to uncover the true mechanisms of stress response and regulation during development. Additionally, our findings support the existence of characteristic stress response profiles as predicted by the ACM model. Abstract : This is the first report to provide evidence of hierarchical stress response coordination among parasympathetic, sympathetic, and HPA axis systems in typically developing adolescents. Findings reveal the need to study stress response dynamics using a multisystem framework.